Impact of surface modification on adsorptive removal of BTX onto activated carbon - Anjum, H. (2019)
The wastewater from chemical industries encapsulates a variety of different volatile organic compounds. Among these hydrophobic pollutants, benzene, toluene and xylene (BTX) are the most harmful organic compounds. The abatement of these deleterious compounds is mandatory. The efficacy of surface modified activated carbon for the uptake of these carcinogenic moieties was analyzed. The commercial activated carbon was functionalized with green oxidizing agents. The structural properties of pristine AC (P-AC) and oxidized AC (O-AC) were analyzed by BET surface area analyzer, Fourier transform infrared spectroscopy-attenuated total reflection (FTIR-ATR), thermogravimetric analysis (TGA), Raman spectroscopy, X-ray diffraction (XRD), and variable pressure field emission scanning electron microscope (VPFESEM). The effect of all the variables namely contact time, temperature, pH and dose was substantially analyzed and optimized. The sorption equilibrium was quickly established within 30 min. The present sorption process conforms to pseudo 2nd order kinetic model and is controlled by intra-particle diffusion. The maximum sorption capacity was computed to be 260.78 mg/g, 263.16 mg/g, 269.55 mg/g for benzene, toluene, and p-xylene respectively, outlining that Langmuir isotherm model fits the data reasonably well as compared to that of Freundlich and D-R model. Furthermore, electrostatic interaction is the plausible mechanism for sorption of BTX onto O-AC. Thus, this mode of functionalization is regarded as the contemporary protocol with high adsorption capacity towards the uptake of BTX as compared to that of previous studies reported in literature. Â© 2019 Elsevier B.V.